2016
DOI: 10.1038/srep35015
|View full text |Cite
|
Sign up to set email alerts
|

Protein-dependent Membrane Interaction of A Partially Disordered Protein Complex with Oleic Acid: Implications for Cancer Lipidomics

Abstract: Bovine α-lactalbumin (BLA) forms cytotoxic complexes with oleic acid (OA) that perturbs tumor cell membranes, but molecular determinants of these membrane-interactions remain poorly understood. Here, we aim to obtain molecular insights into the interaction of BLA/BLA-OA complex with model membranes. We characterized the folding state of BLA-OA complex using tryptophan fluorescence and resolved residue-specific interactions of BLA with OA using molecular dynamics simulation. We integrated membrane-binding data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 68 publications
(111 reference statements)
0
10
0
Order By: Relevance
“…In the context of protein-related diseases, unraveling them is fundamental in order to better understand both the amyloid formation in vivo and the related toxicity [30]. To this aim a great attention has been recently addressed to the interaction between intrinsically disordered regions of proteins and membrane, which may be involved both in protein function and dysfunction in cellular environment [31][32][33].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…In the context of protein-related diseases, unraveling them is fundamental in order to better understand both the amyloid formation in vivo and the related toxicity [30]. To this aim a great attention has been recently addressed to the interaction between intrinsically disordered regions of proteins and membrane, which may be involved both in protein function and dysfunction in cellular environment [31][32][33].…”
Section: Introductionmentioning
confidence: 99%
“…This is a compact denatured state partially retaining the native secondary structure but lacking of a well-defined tertiary structure [39,42] that is known to rapidly insert into the lipid membrane [29,43,44]. Moreover, this state is characterized by a high conformational flexibility [42,45] and thus represents a good model for monitoring protein-membrane interactions in conditions where a stable global protein fold is missing [11,32,46].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…These buried hydrophobic residues are often involved in the interactions with OA in the final liprotide structures and further demonstrate why unfolding of the protein is important. Earlier MD simulations by Chaudhuri and co‐workers suggested that residues from all over aLA interact with OA when aLA is folded . However, Chaudhuri and co‐workers only used a small number of OA molecules, leading to full exposure of individual OA molecules and facilitating interactions between the hydrophobic tail of OA and aLA.…”
Section: Resultsmentioning
confidence: 99%